2015
DOI: 10.1007/s00268-015-3246-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Factors that Patients Use to Choose their Surgeon

Abstract: Patients draw upon a myriad of factors when choosing a surgeon and the circumstances surrounding patients' decisions maybe differ based on sociodemographic, cultural, as well as other factors. Additional information on how patients choose surgeons or hospitals will help providers assist patients in finding their preferred caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 101 publications
11
74
0
1
Order By: Relevance
“…The findings from this exploratory study revealed that individuals who have chronic health conditions still rely primarily on WOM communications through their informal social networks to find information on relevant local resources in their communities. This is consistent with the results of previous research indicating individuals often rely on WOM recommendations for physicians and hospitals (Martin 2017;Yahanda et al 2016). Participants felt this form of information provision was highly personalized, and thus, especially useful to them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings from this exploratory study revealed that individuals who have chronic health conditions still rely primarily on WOM communications through their informal social networks to find information on relevant local resources in their communities. This is consistent with the results of previous research indicating individuals often rely on WOM recommendations for physicians and hospitals (Martin 2017;Yahanda et al 2016). Participants felt this form of information provision was highly personalized, and thus, especially useful to them.…”
Section: Discussionsupporting
confidence: 90%
“…The limitations of existing interventions and technologies may explain why many individuals who have chronic health conditions still rely heavily on word of mouth (WOM) communications and physician recommendations of local resources (such as specialists) rather than going online. The complexities of finding and assessing health information online and determining the credibility and trustworthy of online sources can still be a difficult prospect for many users (Martin 2017;Tu and Lauer 2008;Yahanda et al 2016). However, there may be new opportunities to improve users' experiences searching for information online for local resources in their communities.…”
Section: Searching For Health Information On Local Resourcesmentioning
confidence: 99%
“…A nationally representative survey of U.S. adults revealed that 85% of respondents reported that WOM recommendations from family or friends were a very important or at least somewhat important factor when choosing their physician (Hanauer, Zheng, Singer, Gebremariam, & Davis, ). Similar studies have also demonstrated the importance of WOM recommendations when choosing hospitals (De Cruppé & Geraedts, ; Martin, ); primary care physicians (Tu & Lauer, ); surgeons (Yahanda, Lafaro, Spolverato, & Pawlik, ); cancer specialists (Jiang et al, ); and other types of healthcare providers and resources (McCaughey, McGhan, Walsh, Rathert, & Belue, ; Pettigrew & Durrance, ; Shreffler‐Grant, Weinert, Nichols, & Ide, ). Individuals can draw out highly experiential insights from their family, friends and acquaintances around their satisfaction and dissatisfaction on a wide array of points of care, such as cost, clinical competencies, staff members' interpersonal skills, and more (Martin, ).…”
Section: Introductionmentioning
confidence: 84%
“…Many factors can influence where surgical procedures are undertaken, including distance, hospital attributes, surgeon reputation, wait times, and the preferences of the referring physician. 22,23 However, many of these factors are mitigated by the regionalization of specialist pediatric services to increase case-load volumes, coordination of care, and improve clinical outcomes. 24 Pediatric specialist hospitals perform virtually all of the physiologically complex surgery in most healthcare systems, which is inevitable and by design.…”
Section: Discussionmentioning
confidence: 99%